Efektivitas Bimbingan Kelompok Metode Problem Solving Media Mind Mapping Dalam Perencanaan Karir Siswa - Ahmad, Sirajuddin; Anggriana, Tyas Martika; Christiana, Ratih (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2025)
This study aims to improve students' career planning by using group guidance services with problem solving methods using mind mapping media for class XII students at Senior High School (SMA) Negeri 4 Madiun City. Career planning is something that concerns the long-term future that must be planned well in advance. The method used in this study is an experiment with a one group pretest posttest approach with the Wilcoxon analysis test. The sample in this study was 10 students who were determined using the purposive sampling method. The provision of intervention to students was carried out 3 times with a duration of 45 minutes at each meeting. The significance results of the Wilcoxon analysis test were 0.005 <0.05, which means the difference between before and after the service was given. And the average pretest score of 66 became 101 on the average posttest score, which means that it shows an increase of 8 out of 10 students experiencing a significant increase in career planning. The results of this study indicate that group guidance services using problem solving methods using mind mapping media play a role in providing understanding, knowledge, and information to think systematically and in a planned manner in determining the career planning of class XII students of SMA Negeri 4 Madiun in the 2024/2025 Academic Year effectively.